National rates and disparities in childhood vaccination and vaccine-preventable disease during the COVID-19 pandemic: English sentinel network retrospective database study. Issue 8 (31st March 2022) - Hoang, Uy; de Lusignan, Simon; Joy, Mark; Sherlock, Julian; Williams, John; Bankhead, Clare; Howsam, Gary; Thomas, Mark; Snape, Matthew D; Hobbs, F D Richard; Pollard, Andrew J
Abstract : Objectives: To describe rates and variation in uptake of pneumococcal and measles, mumps and rubella (MMR) vaccines in children and associated change in vaccine-preventable diseases (VPDs) across the first and second waves of the COVID-19 pandemic. Methods: Retrospective database study of all children aged <19 registered with a general practice in the Oxford Royal College of General Practitioners Research and Surveillance Centre English national sentinel surveillance network between 2 November 2015 and 18 July 2021. Results: Coverage of booster dose of pneumococcal vaccine decreased from 94.5% (95% CI 94.3% to 94.7%) at its height on International Organization for Standardization (ISO) week 47 (2020) to 93.6% (95% CI 93.4% to 93.8%) by the end of the study. Coverage of second dose of MMR decreased from 85.0% (95% CI 84.7% to 85.3%) at its height on ISO week 37 (2020) to 84.1% (95% CI 83.8% to 84.4%) by the end of the study. The break point in trends for MMR was at ISO week 34 (2020) (95% CI weeks 32–37 (2020)), while for pneumococcal vaccine the break point was later at ISO week 3 (2021) (95% CI week 53 (2020) to week 8 (2021)). Vaccination coverage for children of white ethnicity was less likely to decrease than other ethnicities. Rates of consultation for VPDs fell and remained low since August 2020. Conclusion: Childhood vaccination rates started to fall ahead of the onset of the second wave; this fall is accentuating ethnic, socioeconomic and geographical disparities in vaccine uptake and risks widening health disparities. Social distancing and school closures may have contributed to lower rates of associated VPDs, but there may be increased risk as these measures are removed. Abstract : Concerns have been raised that immunisation rates for children have fallen during the COVID-19 pandemic. This study finds a <1% fall in immunisation rates for booster pneumococcal and 2nd MMR vaccines during the first 2 pandemic waves. This decrease varied by ethnicity and socio-economic status. Very little vaccine preventable disease occurred during this time. It will be important to continue to monitor trends in childhood vaccination coverage and vaccine preventable disease as the pandemic recedes.